Предмет: Алгебра,
автор: Вероника2346
а³-а²в+ав²-в³
х²-в²-ах-ав
3в+все+3ас+9а
Ответы
Автор ответа:
0
a³-a²b+ab² -b³=a²(a-b)+b²(a-b)=(a-b)(a²+b²)
x²-b²-ax-ab=(x-b)(x+b)-a(x-b)=(x-b)(x+b-a)
3b+bc++3ac+9a=b(3+c)+3a(c+3)=(c+3)(b+3a)
x²-b²-ax-ab=(x-b)(x+b)-a(x-b)=(x-b)(x+b-a)
3b+bc++3ac+9a=b(3+c)+3a(c+3)=(c+3)(b+3a)
Похожие вопросы
Предмет: Алгебра,
автор: hogbanaaaa
Предмет: Химия,
автор: savvsandra
Предмет: Математика,
автор: araikanurtugan5
Предмет: Математика,
автор: asprav1974
Предмет: Математика,
автор: yaelena210257